Determinan Dermatitis Kontak Pekerja pada Perusahaan Pembuatan Slat Pensil - Amelya Karnefi; Rd Halim; Muhammad Syukri; Sri Astuti Siregar; Fahrul Islam (Politeknik Kesehatan Kemenkes Mamuju, 2022)
Dermatitis is the 2nd rank of occupational disease after headache at PT.X (Slate pencil company). Dermatitis in PT X continues to increase every year, in 2017 there were 472 cases, 2018 there were 467 cases and in 2019 it rose to 574 cases. During the last 3 months of 2020, in July there were 30 cases, August there were 35 cases and in September it rose to 38 cases.Workers who suffer from dermatitis experience discomfort at work and experience difficulties and take a long time to complete work. In addition, the number of leave due to dermatitis also increased so that the company's productivity decreased. This study aimed to determine the determinants of contact dermatitis in workers at pencil slat manufacturing companies. This study was an observational study with a cross-sectional design. The population were all workers totaling 210 people. The number of samples of 74 workers who were taken using purposive sampling method with the criteria of permanent workers. The exclusion criteria for this study were workers with contact dermatitis caused by factors other than sawdust. The data were collected using a questionnaire that had been tested for validity and reliability. The results of the study showed that 56.8% of workers experienced contact dermatitis. The determinant factors are the use of PPE (p=0.010), Personal Hygiene (p=0.020), and Working Period (p=0.019). The unrelated factor was Age (= 0.481). Provision of personal protective equipment and supporting equipment for cleanliness of workers in the work area, as well as supervising or monitoring and giving sanctions to workers who do not comply with the use of complete personal protective equipment as well as maintaining personal hygiene.